Engineering ureolytic bacteria for improved microbially induced calcium carbonate precipitation - Goel, Apoorva (Nanyang Technological University, 2023)
Microbially induced calcium carbonate precipitation (MICP) is influenced by various biological and chemical factors. The objective of this study was to understand the biological aspects of Sporosarcina pasteurii DSM33, a model ureolytic bacterium, and engineer it to achieve improved performance of MICP. However, genetic engineering tool for S. pasteurii is unknown, due to which it is difficult to engineer this bacterium. To understand the underlying biological mechanisms behind MICP and potential targets for the genetic engineering, genome analysis of 45 genomes representing Sporosarcina genus, was carried out. Among studied Sporosarcina genomes, 40 were found to have urease genes while 6 genomes were found to have carbonic anhydrase genes depicting the importance of this genus in MICP applications. Further, prospective targets for genetic manipulation such as restriction modification genes, mobile genetic elements and quorum sensing associated genes were analysed. S. koreesnis Q1 and Sporosarcina sp. BP05 were found to be enriched in potential genes that can facilitate the conjugative HGT. Since, genes related to plasmid replicon or conjugative transfer were not detected in S. pasteurii strains, a bioengineering-based approach was adopted to modify the S. pasteurii DSM33. Polydopamine coating which is known for its strong adhesive and biocompatibility was selected for modifying the surface of the S. pasteurii bacterium at nanoscale. The polydopamine coating around S. pasteurii cells resulted in a cell-in-shell structure which showed urea hydrolysis rate of 1250 ± 11 mM/ hr in comparison to uncoated cells with a urea hydrolysis rate of 277 ± 6 mM/ hr. The mechanism of enhanced urease activity was deduced via confocal imaging, molecular techniques and flow cytometry and it was concluded that enhanced permeabilization of cells by polydopamine interaction resulted in increased accessibility of the urease enzyme. Since Ca2+ acts as inhibitor to urease activity, impact of polydopamine coating in protection against Ca2+ inhibition was studied using urease activity assays and bio-consolidation experiments. The strength and water permeability of sand column bio-consolidated by polydopamine coated S. pasteurii were improved in comparison to the sand columns bio-consolidated by uncoated cells. Overall, polydopamine coated cells were found to be effective in increasing mechanical properties of bio-consolidation process.